Efisiensi Faktor Produksi Pada Usahatani Padi Sawah Peserta dan Non-Peserta SL-PTT di Kecamatan Poelang Utara Kabupaten Bombana - Supriono; Sulastri, Rika; Indro Yuwono, Bambang (Agrisurya, 2023)
Research to determine the influence of production factors and their efficiency on rice farming of SL-PTT participants and non-SL-PTT participants and non-SL-PTT participants in North Poleang Bombana District. Carried out in May – July 2011. Samples were determined using simple cluster sampling based on villages, as many as 2 villages (50% of the village population). Respondents from each village consisted of 15 participants and 15 non-participants of SL-PTT in a simple random manner (60 samples). Analysis using multiple non-linear regression using the Cobb-Douglas function and price efficiency analysis. Research results: (a) Production Factors; Land area, amount of use of seeds, fertilizer, labor and pesticides are closely related and simultaneously influence the production of lowland rice farming (R; l 0.889 and R2 = 0.790). (b) partially, except for the number of seeds, all production factors have a positive effect, but only fertilizer has a real effect, even at a confidence level of 85%. (c) Efficiency analysis shows that the use of fertilizer, labor and pesticides is not efficient so they can still be added to improve, while seeds are not efficient.